Technological Achievement, High Technology Exports and Growth - Gani, Azmat (Journal of Comparative International Management)

(untitled) (None, 2009)
The relationship between high technology exports and per capita economic growth in countries with higher levels of technological achievement is examined. Three groups of countries classified as technological leaders, potential leaders and dynamic adopters are chosen for empirical analysis on the basis of the technological achievement index. The regression results reveal that high technology exports exert a statistically significant positive effect on growth of the technological leader category of countries and a positive but statistically insignificant effect on thepotential leader category of countries. The main policy implication is that low-income countries with lower levels of technological achievement and growth may need to focus on new product development with high technological content so as to be competitive in the global trading environment as well as to enhance their growth and development.